Older people's perceptions and experiences of older people with the Sit-to-stand activity: An ethnographic pre-feasibility study - Uirá Duarte Wisnesky; Joanne Olson; Pauline Paul; Sherry Dahlke (Universidade de São Paulo, 2023)
Abstract Objective: the purpose of this pre-feasibility study was to examine perceptions and experiences of a Sit-to-stand activity with urban Brazilian community-dwelling older people in their homes. Method: the exploration method was focused ethnography. Purposive sampling was used to recruit 20 older people. Five means of data generation were used, namely: socio-demographic surveys, participant observations, informal interviews, formal semi-structured interviews, and field notes. Data analysis was qualitative content analysis. Results: the experience of mobility-challenged older people with the Sit-to-stand activity was dependent on their mobility expectations involving many factors that worked together to influence their beliefs and attitudes towards the activity, preferences, behaviors, and cultural perceptions. The participants of this study seemed to find the activity enjoyable; however, the most noticeable shortcomings for their engagement in the Sit-to-stand activity emerged as gaps in their personal and intrapersonal needs. Conclusion: the recommendations generated from the study findings call for the design of implementation strategies for the Sit-to-stand intervention that are tailored to this particular population's needs.